Notch signaling mediates between two pattern-forming processes during head regeneration in Hydra - Steichele, Mona; Sauermann, Lara; Pan, Qin; Moneer, Jasmin; Porte, Alexandra de la; Heß, Martin; Mercker, Moritz; Strube, Catharina; Flaswinkel, Heinrich; Jenewein, Marcell; Böttger, Angelika (Life science alliance, 2025)
Hydra head regeneration consists of hypostome/organizer and tentacle development, and involves Notch and Wnt/β-catenin signaling. Notch inhibition blocks hypostome/organizer regeneration, but not the appearance of the tentacle tissue. β-Catenin inhibition blocks tentacle, but not hypostome/organizer regeneration. Gene expression analyses during head regeneration revealed the Notch-promoting expression of HyWnt3, HyBMP2/4, and the transcriptional repressor genes CnGsc, Sp5, and HyHes, while blocking HyBMP5/8b and the c-fos-related gene HyKayak. β-Catenin promotes the expression of the tentacle specification factor HyAlx, but not of HyWnt3. This suggests HyWnt3 and HyBMP4 as parts of a hypostome/organizer gene module, and BMP5/8, HyAlx, and β-catenin as parts of a tentacle gene module. Notch then functions as an inhibitor of tentacle production to allow regeneration of a hypostome/head organizer. HyKayak is a candidate target gene for HvNotch-induced repressor genes. Inhibiting HyKayak attenuated the expression of HyWnt3. Polyps of Craspedacusta do not have tentacles and thus after head removal only regenerate a hypostome structure. Notch signaling was not needed for head regeneration in Craspedacusta, corroborating the idea of its requirement during Hydra head regeneration to harmonize two co-operating pattern-forming processes.